The Effect of Authentic Leadership and Job Insecurity on Turnover Intention: : A Quantitative Study of Indonesian Public Service Organizations - Novina Sabila Zahra; Afzal Sayed Munna; Abdul Kadir; Denok Sunarsi; Sri Rochani Mulyani; Aryanti Ratnawati; Julizar Idris; Duratul Ain Tholibon (International Journal of Educational Administration, Management, and Leadership, 2022)
This research aimed to determine the effect of authentic leadership and job insecurity on turnover intention. Turnover intention still becomes one of the issues in public service organisations. Despite the fact that Indonesian employees in public organizations are more stable than their business counterparts, many employees develop the intention to quit their job as public service providers. This study recruited 231 employees from public organisations in Indonesia (hospitals, schools, et cetera.), with 87 males (38%) and 144 females (62%). The participants' average age is 32.39 (SD = 13.37), they have 10 years of service (SD = 10.52), and the most recent education is a diploma and/or bachelor's degree (64%). Hierarchical multiple regression was used to analyse the data. The findings revealed that job insecurity affected turnover intention, while authentic leadership had no effect. According to the study's findings, employees of public organisations who feel comfortable at work are likelier to stay and have a low desire to quit. Therefore, public organisations must pay attention to factors that may lead to job insecurity for employees to survive.